Respuesta :

assumin you mean

[tex]\frac{x^4-1}{x+1}[/tex]
recognize difference of 2 perfect squares
remember that [tex]a^2-b^2=(a+b)(a-b)[/tex]

so
factor the numerator
[tex]x^4-1=(x^2)^2-(1)^2=[/tex] [tex] (x^2+1)(x^2-1)[/tex]
but look, another perfect square
[tex](x^2+1)(x^2-1)=(x^2+1)(x^2-1^2)=(x^2+1)(x+1)(x-1)[/tex]
so we end up with

[tex]\frac{x^4-1}{x+1}=\frac{(x^2+1)(x-1)(x+1)}{x+1}[/tex] which simplifies to [tex](x^2+1)(x-1)[/tex]
x^4/x + 1
Steps
Divide x^4/x + 1: x^4/x + 1 = x^3 + -x^3/x +1
= x^3 + -x^3/x +1
Divide -x^3/x + 1: -x^3/x + 1 = -x^2 + x^2/x + 1
= x^3 - x^2 + x^2/x + 1
Divide x^2/x +1: x^2/x + 1: x^2/x + 1 = x + -x/x + 1
= x^3 - x^2 + x + -x/x +1
Divide -x/x + 1: -x/x + 1 = -1 + 1/x + 1
= x^3 - x^2 + x - 1 + 1/x + 1